Impact of Enterprise Resource Planning System on The Quality of Accounting Information at Enterprises in Vietnam - Dang, Lan Anh (Archives of Business Research, 2024)
The research aims to explore the impact of Enterprise Resource Planning (ERP) systems on the quality of accounting information in businesses in Vietnam. Through surveying managers and accounting departments at large-scale enterprises that have applied ERP, the author uses SPSS and AMOS tools to analyze collected data. Research results have shown that ERP has a strong impact on the quality of accounting information. From there, the author proposes policy implications for the Vietnamese government and businesses to raise awareness and apply ERP effectively, thereby contributing to improving the quality of accounting information.